1996
DOI: 10.1111/j.1524-4725.1996.tb00373.x
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Copper-Bromide Laser for Treating Telangiectasia

Abstract: The copper bromide laser was an effective tool in the treatment of certain cutaneous vascular lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…[2][3][4] In addition to PDL, other lasers, including potassium titanyl phosphate, 532-nm Nd:YAG, 1064-nm Nd:YAG, argon, copper-bromide, and intense pulsed light have been used in treatment of facial telangiectasia. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] PDLs have been proven safe and effective in the treatment of a variety of vascular lesions. The laser selectively targets vascular structure through selective light absorbed by oxyhemoglobin and pulse duration that prevents damage to the epidermis and surrounding dermis.…”
mentioning
confidence: 99%
“…[2][3][4] In addition to PDL, other lasers, including potassium titanyl phosphate, 532-nm Nd:YAG, 1064-nm Nd:YAG, argon, copper-bromide, and intense pulsed light have been used in treatment of facial telangiectasia. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] PDLs have been proven safe and effective in the treatment of a variety of vascular lesions. The laser selectively targets vascular structure through selective light absorbed by oxyhemoglobin and pulse duration that prevents damage to the epidermis and surrounding dermis.…”
mentioning
confidence: 99%
“…1,2 The earliest lasers used for telangiectases and other vascular lesions were the continuous-wave argon (488 and 514 nm), 5-8 the continuous-wave carbon dioxide (10,600 nm), 8 and the neodymium (Nd):YAG (1064 nm) 8,9 lasers. Recently, other yellow-light lasers such as argon pumped tunable dye, 17,18 copper vapor, 19,20 copper bromide, 21 and krypton 22 lasers have been shown to be effective in the treatment of telangiectases. However, the vessels do not preferentially absorb the energy they emit and heat is delivered to adjacent tissues.…”
mentioning
confidence: 99%
“…The beam is interrupted by a mechanical shutter resulting in exposure times from 7 msec up to 6 sec. The authors concluded that the copper bromide laser produced results similar to those achieved with the pulsed dye laser for most facial telangiectasias without purpura or hyperpigmentation (30)(31)(32). In a study performed by McCoy et al (30), 23 subjects obtained good to excellent results following treatment of benign vascular lesions on the head, neck, and anterior chest with the copper bromide laser.…”
Section: Copper Bromide Lasermentioning
confidence: 92%
“…The shutter speed generally employed results in 2.5-3 pulses/sec (tissue exposure durations of 300-400 msec) with energy densities ranging from 13 to 36.4 J/cm 2 (30). The beam is interrupted by a mechanical shutter resulting in exposure times from 7 msec up to 6 sec.…”
Section: Copper Bromide Lasermentioning
confidence: 99%